2016
DOI: 10.1371/journal.pmed.1002167
|View full text |Cite
|
Sign up to set email alerts
|

Measures of Malaria Burden after Long-Lasting Insecticidal Net Distribution and Indoor Residual Spraying at Three Sites in Uganda: A Prospective Observational Study

Abstract: BackgroundLong-lasting insecticidal nets (LLINs) and indoor residual spraying of insecticide (IRS) are the primary vector control interventions used to prevent malaria in Africa. Although both interventions are effective in some settings, high-quality evidence is rarely available to evaluate their effectiveness following deployment by a national malaria control program. In Uganda, we measured changes in key malaria indicators following universal LLIN distribution in three sites, with the addition of IRS at one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
165
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(188 citation statements)
references
References 33 publications
(40 reference statements)
7
165
1
1
Order By: Relevance
“…This finding contradicts findings from other studies that have reported ITN efficacy [32,34,35] and effectiveness [2,16,36,37]. However, these results are consistent to recent findings for Burkina Faso [12], Nigeria [11], Tanzania [9], and Senegal [10].…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…This finding contradicts findings from other studies that have reported ITN efficacy [32,34,35] and effectiveness [2,16,36,37]. However, these results are consistent to recent findings for Burkina Faso [12], Nigeria [11], Tanzania [9], and Senegal [10].…”
Section: Discussioncontrasting
confidence: 72%
“…Uganda has the fourth highest number of Plasmodium falciparum infections [1] and some of the highest reported malaria transmission rates in the world [2]. Ninety five percent of the country has stable malaria transmission, with the rest having low and unstable transmission with potential for epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…The sites differed markedly, with very high transmission intensity, parasite prevalence, and malaria incidence in Tororo District, lower levels of all of these parameters in Kanungu District, and the lowest levels in Jinja District. Of note, malaria transmission was considerably greater in earlier surveys of Jinja District, and transmission has since decreased greatly in Tororo District after a campaign of indoor residual spraying of insecticide that was launched in 2014 (Katureebe et al, 2016). Historically, it appears that malaria transmission intensity followed the rank order Tororo > Jinja > Kanungu (Yeka et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The three Ugandan study sites differed greatly in recent malaria transmission intensity (Kamya et al, 2015; Katureebe et al, 2016). Tororo District has had very high transmission intensity recorded, with entomologic inoculation rates >300 infectious bites per year, although very recently transmission intensity has decreased due to an intensive IRS campaign.…”
Section: Discussionmentioning
confidence: 99%
“…This is a much lower frequency than observed in other vector mosquitoes where carbamates are routinely used in vector control 58 . Whilst insecticides linked to selection of A ce- 1 resistant alleles have not been officially applied for vector control in the studied area for over one decade 59,60 indoor residual spraying (IRS) using bendiocarb was conducted in Tororo from December 2014 - February 2015 61,62 , after the period of collection of these samples, and hence this allele frequency is higher than expected. Nevertheless, an indirect source of insecticide exposure due to agricultural activities could also be shaping the insecticide resistance as described for C. quinquefasciatus populations from Iran 63 .…”
Section: Discussionmentioning
confidence: 97%